2014
DOI: 10.1590/s1517-83822014000200028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental stress on biochemical parameters of bacteria reducing chromium

Abstract: Chromium pollution is produced in connection with industrial processes like in tanneries. It has been suggested that bioremediation could be a good option for clean up. The stress effect of variable chromate levels, pHs and growth temperatures on biochemical parameters of two Cr(VI) reducing bacterial strains Pseudomonas aeruginosa Rb-1 and Ochrobactrum intermedium Rb-2 was investigated. Transmission electrone microscopy (TEM) was performed to study the intracellular distribution of Cr(VI). It was observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The results obtained from TEM analysis of B. subtilis MNU16 demonstrated the allocation of FDP inside and outside cells which might be due to the exposure of hexavalent chromium treatments. Similarly, study conducted by Batool et al (2014) reported similar pattern of FDP and cell disruption in cells of P. aeruginosa and Ochrobactrum intermedium treated with different concentrations of Cr(VI). Further, in the present study, the deposition of EDP inside the B. subtilis MNU16 might be due to the accumulation and intracellular reduction of Cr(VI) as shown in Figures 2C,D .…”
Section: Discussionsupporting
confidence: 60%
“…The results obtained from TEM analysis of B. subtilis MNU16 demonstrated the allocation of FDP inside and outside cells which might be due to the exposure of hexavalent chromium treatments. Similarly, study conducted by Batool et al (2014) reported similar pattern of FDP and cell disruption in cells of P. aeruginosa and Ochrobactrum intermedium treated with different concentrations of Cr(VI). Further, in the present study, the deposition of EDP inside the B. subtilis MNU16 might be due to the accumulation and intracellular reduction of Cr(VI) as shown in Figures 2C,D .…”
Section: Discussionsupporting
confidence: 60%
“…As both bacterial strains were normally maintained on chromate supplemented media so chromate was accumulated intra‐cellularly. In routine, these strains were maintained on chromate supplemented medium so when the cells were grown in the chromate free medium, the intra‐cellularly accumulated Cr(VI) was reduced to Cr(III) and deposited on the periphery of bacterial cell walls . 13 C NMR spectrum of EPS produced by P. aeruginosa Rb‐1 and O. intermedium Rb‐2 under stress and stress free conditions showed that EPS may be a glucan.…”
Section: Discussionmentioning
confidence: 99%
“…For FTIR analysis, all EPS fractions were centrifuged and lyophilized, followed by weighing. Then 20 mg of finely ground EPS fraction was used to get the information specific to the functional groups by KBr disc method .…”
Section: Methodsmentioning
confidence: 99%
“…Similar observations were made during transitional elemental supplementation reducing the viability of B. subtilis , C. rubrum and Pseudomonas sp. (Vijayalakshmi et al 2011 ; Batool et al 2014 ).…”
Section: Resultsmentioning
confidence: 99%